ANALISIS KOHESI SOSIAL KELUARGA KAWIN CAMPUR ETNIS DAYAK DAN TIONGHOA DI DUSUN PANCAROBA - Pramesti, Sally Tilana; Fatmawati, Fatmawati; Imran, Imran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research purpose is to investigate, the ?social cohesion?of intermarriage between Dayak and Tionghoa ethnic in Pancaroba hamlet, Pancaroba village. General problem in this research is social cohesion in intermarriage between Dayak and Tionghoa ethnic. This research purpose is to describe social cohesion is similar fate, moral commitment and mutual trust. This research use qualitative approach with descriptive method. Data collection is done with observation, interview and documentation. Data source used is primary and secondary data.techic used for analiyzing data is data reduction, data display, and decision making and verification. Result from this research show that : 1. Social cohesion in similar fate from Dayak and Tionghoa ethcnic intermarriage, is job which have same job as, merchant only one intermarriage family have job as rubben farmer and Dayak Kanayatn dominant kinship system.2 social cohesion intermarriage. Moral commitmen from Dayak and Tionghoa ethnic is more custums from intermarriage family which celebrate chinesee new year, grave prayer, gawai dayak and ruah and tolerate for celebrate chinesee new year and grave prayer. 3 social cohesion mutual. Trust is commitment and communication that intermarriage family agredd that Dayak Kanayatn etchic is more dominat and everyday language used for everyday language is ahe language. Keywords:Ethnic, Intermarriage, Social Cohesion,